Empowering Citizens with Learning Disabilities to Build Entrepreneurship at the Community Learning Center of Rumpun Aksara - Ayuni, Dias; Alkornia, Sylva; Himmah, Irliana Faiqotul (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
Equitable and equitable education for people with disabilities in Jember Regency is still not well implemented. Therefore, PKBM Rumpun Aksara as a non-formal educational institution also opens up access to education for people with disabilities to gain knowledge and skills. These skills are adapted to the background of students with disabilities, the majority of whom are entrepreneurs and have obstacles in their business. So the aim of this research is to describe the empowerment of students with disabilities in building entrepreneurial independence at PKBM Rumpun Aksara. The method in this research uses a descriptive method with a qualitative approach. Determining the research location used a purposive area technique, namely at PKBM Rumpun Aksara. Data collection uses observation, interview and documentation techniques. The conclusions in this research show that the empowerment carried out by PKBM Rumpun Aksara can build entrepreneurial independence for students with disabilities who are characterized by a work ethic, being able to meet their needs, not depending on other people, and initiative